(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
This text presents a sharing of experiences and theoretical-practical questions about artistic and pedagogical processes for animation theater in cyberspace, developed both in the conventional pedagogical environment (Animation Theater discipline at Faculdade de Artes do Paraná, from Universidade Estadual do Paraná FAP-UNESPAR - Paraná State University), and at Cia Laica de Teatro, in which I work as a director. For such, the approach divides and sequentially presents the actions, in a modality with the aim of systematizing the procedures. This text presents a sharing of experiences and theoretical-practical questions about artistic and pedagogical processes for animation theater in cyberspace, developed both in the conventional pedagogical environment (Animation Theater discipline at Faculdade de Artes do Paraná, from Universidade Estadual do Paraná FAP-UNESPAR - Paraná State University), and at Cia Laica de Teatro, in which I work as a director. For such, the approach divides and sequentially presents the actions, in a modality with the aim of systematizing the procedures.